Factors Related to Prevention and Control of Hand Foot and Mouth Disease of Responsible Person in Private Kindergartens, Bangkok - ศรีจักร์, เกษสุดา; แสงสว่าง, ภูเบศร์ (Journal of Health Science of Thailand, 2021)
Hand Foot and Mouth disease is commonly found in children aged under 5 years or preschool. The trend has been increased every year and has affected well-being of children. The private kindergarten in Bangkok is a place where the childrens spent time together, to employed prevent and control of the disease the standard guideline by the responsible person is important that could affect the spread of the disease. This study cross-sectional research design aimed at investigated factors affecting the prevention and control of hand foot and mouth disease of responsible person in private kindergarten, Bangkok. A sample of responsible personal at private kindergarten, Bangkok were recruited 150 and were collected during February - March 2019. Data were asked to self- administed questionnaires and analyzed by descriptive statistics and Chi-square test. The result revealed that the majority of participants age between 30-39 years (32.7%), female gender (82.0%) and were teachers (52.4%). Prevention and control of hand foot and mouth disease of the private kindergartens were nearly good (72 %). Factors significantly associated with the prevention and control of hand foot and mouth disease included: 1) educational background (p=0.038), 2) past training history (p=0.001), 3) knowledge related to hand foot mouth disease (p=0.001), 4) job assignment of the organizational structure (p=0.001), 5) knowledge information 6) materials support and equipment from public health personnel (p=0.001) and 7) participation of parents and communities (p=0.001). Therefore, effective weakness to prevent and control of hand foot mouth disease in private kindergarten consisted of enhancing current relevant knowledge and information of the responsible staff in the private kindergarten, encouraging parents and community in volunteer, include material and equipment support. Finally, collaboration between public sector and private sectors for follow-ups and evaluations is key component to ensure successful operation.